Implementation of the nursing process in clinical practice: learning experience - Silva, Marcos Barragan da; Meneghete, Maria Cristina; Fontana, Rosane Teresinha (Revista de Enfermagem UFPE on line, 2010)
ABSTRACT Objectives: to describe the academic experience on the implementation of the nursing process in a clinical unit, locus where this practice is not performed. Methodology: a descriptive study, which reports an experiment conducted with nurses and a nursing service in adult clinic of a hospital in Rio Grande do Sul/BR. Data were collected by instruments built for the application of nursing process and observations. For the analysis we used descriptive statistics. The study followed the ethical principles established by Resolution 196/96 of the National Health Council and was approved by the Ethics Committee of the Regional Integrated University of High Uruguay and Missions - Campus Santo Ângelo/RS, under Protocol 120-04/TCH / 07. Results: experience has shown the importance of systematic care as a foundation for effective practice of nursing as a scientific and passed along to the team as it allowed for further reflection, allowing the academic practice of the nursing process. Conclusion: the experiences in fertile scenario for the implementation of actions such as this can contribute to the practice, as it enables the development of critical and reflective future nurse, on which derive positive implications for nursing. Descriptors: nursing process; nursing practical, students nursing; nursing diagnosis; nursing assessment. RESUMO Objetivos: descrever a vivência acadêmica acerca da implementação do processo de enfermagem em uma unidade clínica, lócus onde esta prática não é realizada no cotidiano profissional. Metodologia: estudo descritivo, que relata uma experiência desenvolvida com enfermeiros e técnicos de um serviço de enfermagem clínica adulto de um hospital do interior do Rio Grande do Sul/BR. Os dados foram coletados a partir de instrumentos construídos para aplicação do Processo de Enfermagem e de observações. Para a análise utilizou-se a estatística descritiva. O estudo cumpriu os princípios éticos estabelecidos pela Resolução 196/96 do Conselho Nacional de Saúde e obteve parecer favorável do Comitê de Ética da Universidade Regional Integrada do Alto Uruguai e das Missões - Campus Santo Ângelo-RS, sob protocolo nº 120-04/TCH/07. Resultados: a experiência demonstrou a importância da sistematização do cuidado como alicerce para a efetivação da enfermagem como prática científica e repercutiu junto à equipe na medida em que permitiu reflexões, possibilitando ao acadêmico a prática do processo de enfermagem. Conclusão: a vivencia em cenários férteis para a implantação de ações como esta, pode contribuir para a práxis, na medida em que possibilita o desenvolvimento crítico-reflexivo do futuro enfermeiro, sobre a qual advêm implicações positivas para a enfermagem. Descritores: processos de enfermagem; enfermagem prática; estudantes de enfermagem; diagnóstico de enfermagem; avaliação em enfermagem. RESUMEM Objetivos: describir la experiencia académica en la aplicación del proceso de enfermería en una unidad clínica, lugar donde esta práctica no se realiza. Metodología: estudio descriptivo, que informa de un experimento realizado con enfermeras y un servicio de enfermería clínica de adultos de un hospital de Rio Grande do Sul / BR. Los datos fueron recogidos de los instrumentos construidos para la aplicación del proceso de enfermería y observaciones. Para el análisis se utilizó la estadística descriptiva. El estudio siguió a los principios éticos establecidos por la Resolución 196/96 del Consejo Nacional de Salud y fue aprobado por el Comité de Ética de la Universidad Regional Integrada del Alto Uruguay y Misiones - Campus Santo Ângelo, RS, en virtud del Protocolo 120-04/TCH / 07. Resultados: la experiencia ha demostrado la importancia de la atención sistemática como base para la práctica efectiva de la enfermería como científicos y se trasmite al equipo ya que permite una mayor reflexión, lo que permite la práctica académica del proceso de enfermería. Conclusión: las experiencias en cenario fértil para la aplicación de estas medidas ya que esto puede contribuir a la práctica, ya que permite el desarrollo de la futura enfermera crítica y reflexiva, en la que se derivan consecuencias positivas para la enfermería. Descriptores: procesos de enfermería; enfermería práctica; estudiantes de enfermería; diagnóstico de enfermeria; evaluación en enfermería.